Acute Exercise and Motor Memory Consolidation: The Role of Exercise Timing. (3rd July 2016) - Thomas, Richard; Beck, Mikkel Malling; Lind, Rune Rasmussen; Korsgaard Johnsen, Line; Geertsen, Svend Sparre; Christiansen, Lasse; Ritz, Christian; Roig, Marc; Lundbye-Jensen, Jesper
Abstract : High intensity aerobic exercise amplifies offline gains in procedural memory acquired during motor practice. This effect seems to be evident when exercise is placed immediately after acquisition, during the first stages of memory consolidation, but the importance of temporal proximity of the exercise bout used to stimulate improvements in procedural memory is unknown. The effects of three different temporal placements of high intensity exercise were investigated following visuomotor skill acquisition on the retention of motor memory in 48 young (24.0 ± 2.5 yrs), healthy male subjects randomly assigned to one of four groups either performing a high intensity (90% Maximal Power Output) exercise bout at 20 min (EX90), 1 h (EX90+1), 2 h (EX90+2) after acquisition or rested (CON). Retention tests were performed at 1 d (R1) and 7 d (R7). At R1 changes in performance scores after acquisition were greater for EX90 than CON (p < 0.001 ) and EX90+2 (p = 0.001 ). At R7 changes in performance scores for EX90, EX90+1, and EX90+2 were higher than CON (p < 0.001, p = 0.008, and p = 0.008, resp.). Changes for EX90 at R7 were greater than EX90+2 (p = 0.049 ). Exercise-induced improvements in procedural memory diminish as the temporal proximity of exercise from acquisition is increased. Timing of exercise following motor practice is important for motor memory consolidation.